Exploring Educational Diversity: A Comparative Analysis of Indonesia with Europe and America - Hasanah, Hani; Al Faruq Abdullah, Muhamad; Madhakomala, R. (Greenation Research & Yayasan Global Resarch National, 2024)
This study aims to analyze a comparative perspective of education systems in Indonesia, Europe, and America. The main focus is to identify differences in educational approaches, curriculum structures, teaching methods, and the challenges faced by Indonesia in enhancing its education quality and global competitiveness. A qualitative library research method was employed, reviewing literature related to the education systems of the three regions. The results show that Europe emphasizes equitable access, flexibility, and competency-based education tailored to local needs. In contrast, the United States adopts a decentralized system, encouraging student freedom in course selection and non-academic skill development through extracurricular activities. Meanwhile, Indonesia applies a more centralized curriculum focusing on uniformity and cultural-moral values. Indonesia’s main challenges include achieving equitable access to quality education, improving teacher capacity, and integrating technology into learning processes. This conclusions represent that Indonesia can adopt best practices from Europe and America, such as curriculum flexibility, competency-based approaches, and technology utilization, to create a more innovative and inclusive education system.